Consumer Ratings of the Most Desirable Hearing Aid Attributes - Manchaiah, Vinaya; Picou, Erin M.; Bailey, Abram; Rodrigo, Hansapani (Journal of the American Academy of Audiology, 2021)
Background Modern hearing aids have various features and functionalities, such as digital wireless streaming, bilateral connectivity, rechargeability, and specialized programs, which allow for a multitude of hearing aid attributes (e.g., comfort, reliability, and clarity). Consumers likely vary greatly in their preferences for these hearing aid attributes. Their preferences might be related to various demographic and hearing loss characteristics.Purpose The purposes of this study were to describe which hearing aid attributes consumers find desirable when choosing their hearing aids and to explore factors that might predict preferences.Research Design Cross-sectional.Study Sample 14,993.Intervention Not applicable.Data Collection and Analysis In this retrospective study, hearing aid attribute preferences were evaluated from consumers who answered questions in the Help Me Choose tool on the HearingTracker.com Web site. Chi-squared tests and correlation analyses were used to identify potential relationships between attribute preference and respondent characteristics. Cluster analysis with Partitioning Around Medoids (PAM) was used to identify patterns of attribute preferences.Results Of the 21 hearing aid attributes queried, the four most favorably rated were improved ability to hear friends and family in quiet and in noisy settings, physical comfort, and reliability, with 75 to 88% of respondents rating these attributes as very or extremely important. Type of hearing loss, technology level preference, and mobile phone brand were significantly associated with preferences for all 21 hearing aid attributes. PAM cluster analysis unveiled two unique user groups based on their preference to hearing aid attributes. One-third of the respondents preferred high-end technology and favored all types of advanced attributes. The other two-thirds of users predominantly preferred either advanced or best match and were more selective about which attributes were most important to them.Conclusion Patterns in preferences to hearing aid attributes help identify unique subgroups of consumers. Patient preferences for specific hearing aid attributes, in addition to audiologic characteristics, could help audiologists in recommending hearing aids for their patients.
Keywords: hearing aid attributes; hearing aid features; consumer preferences